2013
DOI: 10.1007/s00415-013-6831-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroborreliosis-associated cerebral vasculitis: long-term outcome and health-related quality of life

Abstract: Neuroborreliosis affects the nervous system after systemic infection with the spirochete Borrelia burgdorferi. Previously, cerebral vasculitis has been regarded as an extremely rare complication of neuroborreliosis. The data on the long-term outcome in patients with cerebral vasculitis due to neuroborreliosis are limited. The objective of this study was to perform a longitudinal analysis of cases of neuroborreliosis-associated cerebral vasculitis. We recruited all patients (n = 11) diagnosed with neuroborrelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 22 publications
2
35
1
4
Order By: Relevance
“…9,14,23,28,31 Signs of arachnoiditis, contrast enhancement in the blood vessel wall, and abnormalities of artery caliber observed on MRI support the hypothesis of vasculitis, sometimes confirmed by conventional angiography. 3,10,14,16,22,33,35 Possible radiological findings are both ischemic and hemorrhagic, and nonspecific. However, the multiterritorial aspect of strokes and signs of vasculitis may also be suggestive of a diagnosis of neuroborreliosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…9,14,23,28,31 Signs of arachnoiditis, contrast enhancement in the blood vessel wall, and abnormalities of artery caliber observed on MRI support the hypothesis of vasculitis, sometimes confirmed by conventional angiography. 3,10,14,16,22,33,35 Possible radiological findings are both ischemic and hemorrhagic, and nonspecific. However, the multiterritorial aspect of strokes and signs of vasculitis may also be suggestive of a diagnosis of neuroborreliosis.…”
Section: Discussionmentioning
confidence: 97%
“…5,13,33 Prognosis is mainly associated with the stroke localization as posterior circulation is associated with a poorer prognosis. 3 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[46][47][48] In Europe, clinical studies have reported signs of polyneuropathy in 40-60% of patients who present with a pathognomonic late cutaneous manifestation of Lyme disease, acrodermatitis chronica atrophicans (ACA). [49][50][51] The ACA-associated polyneuropathy is asymmetric and predominantly sensory, and usually follows the skin lesion.…”
Section: Manifestations and Diagnosismentioning
confidence: 99%
“…Enfin, au cours de la phase tertiaire de la maladie de Lyme, l'action directe de Borrelia burgdorferi est encore possible, mais les phénomènes dysimmunitaires participent essentiellement à la persistance des lésions neurologiques. Les complications neurologiques peuvent être centrales, sous la forme d'encéphalomyélites progressives (4-10 % des patients atteints de neuroborrélioses), d'accidents vasculaires cérébraux ou de tableaux pouvant mimer une maladie de Horton en rapport avec une vascularite cérébrale (0,3 % des cas), de troubles cognitifs ou encore de neuropathies périphériques [2,5,6,21,22].…”
Section: Discussionunclassified